Evaluation of the zootechnical performance of broiler chicken at the level of different types of breeding in Algeria - Lamari, Sara (Algerian Journal of Biosciences, 2023)
The objective of this work was to study the influence of livestock farming type on the performance of broilers chickens (COBB 500 strains) in the semi-arid region of Sétif in Algeria. It has been determined the zootechnical parameters of chickens (live weight (g), Average daily gain, Consumption Index, Mortality) for control of livestock farming type. Indeed, the growth of broiler chickens was influenced by livestock farming type; the live weight and the average daily gain respectively were linked to livestock farming type (p < 0.05). Whereas the consumption Index was close to the meaning (p=009). Broiler chickens of larges breeders had more growth performance with heavy carcasses (2872, 22±251,39 g), the more the average daily gain (61,94±7,23 g/day), and better consumption index (1,76 ± 0,16) at 47 days of age. The mortality rate, in fact, is high and exceeds 10%. The efforts must be concentrated on equipping buildings, hygiene rules and health programs, strengthening the training of the human factor to obtain the best performance from the broiler chicken: a low mortality rate, better weight growth and an improved consumption index